2001
DOI: 10.1093/nar/29.8.1690
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in polyadenylation cleavage sites in mammalian mRNA sequences: implications for SAGE analysis

Abstract: The analysis of a human thyroid serial analysis of gene expression (SAGE) library shows the presence of an abundant SAGE tag corresponding to the mRNA of thyroglobulin (TG). Additional, less abundant tags are present that can not be linked to any other known gene, but show considerable homology to the wild-type TG tag. To determine whether these tags represent TG mRNA molecules with alternative cleavage, 3′-RACE clones were sequenced. The results show that the three putative TG SAGE tags can be attributed to T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 17 publications
5
90
0
Order By: Relevance
“…This "clean" set was then mapped onto the genome sequences and genomelinked tags were derived by combining the 50 nt 3Ј tag with the 50 nt following the tag in the genome (the total genomelinked tag length is thus 100 nt). These combined tags were clustered to resolve short-range variations in the exact polyadenylation site between individual transcript sequences; it should be noted that this procedure eliminates from our analysis the short-range variation shown by Pauws et al (2001). After clustering, 13% of the tags identified genome regions with nonidentical downstream sequences.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This "clean" set was then mapped onto the genome sequences and genomelinked tags were derived by combining the 50 nt 3Ј tag with the 50 nt following the tag in the genome (the total genomelinked tag length is thus 100 nt). These combined tags were clustered to resolve short-range variations in the exact polyadenylation site between individual transcript sequences; it should be noted that this procedure eliminates from our analysis the short-range variation shown by Pauws et al (2001). After clustering, 13% of the tags identified genome regions with nonidentical downstream sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Although there have been numerous reports in the literature of transcripts undergoing alternative polyadenylation involving relatively distant sites (van Eyndhoven et al 1998;Coy et al 1999;Touriol et al 1999), it was unexpected to observe it at this high frequency. Estimates gathered from EST clustering alone (Gautheret et al 1998;Beaudoing and Gautheret 2001;Pauws et al 2001). We experimentally verified our methodology by performing reverse transcriptasepolymerase chain reaction (RT-PCR) experiments on the predicted long 3Ј UTRs of the WDR9 (WD repeat 9) and KCNJ5 (potassium inwardly rectifying channel 5) genes and found that they do indeed encode transcripts extending far downstream from the 3Ј ends documented by "full-length" cDNA sequences, even though the intervening regions are not fully covered by ESTs (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations